2021
DOI: 10.1093/geronb/gbab097
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Self-Administered Online Cognitive Assessment in Detecting Amnestic Mild Cognitive Impairment

Abstract: Objectives Our aim was to validate the online Brain Health Assessment (BHA) for detection of amnestic mild cognitive impairment (aMCI) compared to gold-standard neuropsychological assessment. We compared the diagnostic accuracy of the BHA to the Montreal Cognitive Assessment (MoCA). Methods Using a cross-sectional design, community-dwelling older adults completed a neuropsychological assessment, were diagnosed as normal cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 38 publications
0
27
1
Order By: Relevance
“…As such, factors such as ageappropriate stimuli, and familiarity with computers were taken into account when designing and extensively piloting the web-based platform (Troyer et al, 2014). Second, it was psychometrically validated, which is rare for online tests, and confirmed that the test consistently obtained the same results when repeated (reliability), and that it measures what it attempts to measure (validity; Paterson et al, 2021;Troyer et al, 2014). Lastly, it was developed as a screening tool for memory concerns, and reliably distinguishes people who are 'worried well' from those who should be seeing a health care professional.…”
Section: Project Overview and Contextmentioning
confidence: 85%
“…As such, factors such as ageappropriate stimuli, and familiarity with computers were taken into account when designing and extensively piloting the web-based platform (Troyer et al, 2014). Second, it was psychometrically validated, which is rare for online tests, and confirmed that the test consistently obtained the same results when repeated (reliability), and that it measures what it attempts to measure (validity; Paterson et al, 2021;Troyer et al, 2014). Lastly, it was developed as a screening tool for memory concerns, and reliably distinguishes people who are 'worried well' from those who should be seeing a health care professional.…”
Section: Project Overview and Contextmentioning
confidence: 85%
“…Online testing allows collection of a large sample of individuals from different ages, to gain insights on how risk factor effects vary by age. The online assessment we used has been psychometrically validated, and demonstrated adequate internal consistency, test-retest reliability, alternate version reliability, and construct validity [22], plus adequate convergent validity when compared to clinician-administered neuropsychological tests of the same constructs [23]. Moreover, the test was designed to be suitable for older adults [22], and also provides greater sensitivity at the high end of function [23] than the Montreal Cognitive Assessment [24], offering sensitivity to assess a relatively healthy sample.…”
Section: Lifespan Cognitive Effects Of Dementia Risk Factorsmentioning
confidence: 99%
“…The online assessment we used has been psychometrically validated, and demonstrated adequate internal consistency, test-retest reliability, alternate version reliability, and construct validity [22], plus adequate convergent validity when compared to clinician-administered neuropsychological tests of the same constructs [23]. Moreover, the test was designed to be suitable for older adults [22], and also provides greater sensitivity at the high end of function [23] than the Montreal Cognitive Assessment [24], offering sensitivity to assess a relatively healthy sample. The use of measures ostensibly sensitive to downstream effects of dementia risk factors was achieved by the combination of online testing (to obtain large sample sizes) and a sensitive assessment suited to detect changes in people with risk factors (e.g., distributed damage due to subtle vascular brain changes, white matter changes, and reduced reserve capacity, leading to earlier onset of clinically-evident neurodegeneration [25]).…”
Section: Lifespan Cognitive Effects Of Dementia Risk Factorsmentioning
confidence: 99%
“…The assessment was developed to be suitable for older adults, and was psychometrically validated showing acceptable internal consistency, test-retest reliability, and alternate version reliability (38). It also showed good construct validity compared to traditional neuropsychological tests of the same constructs, and sensitivity at the higher end of function, making it suitable to assess a relatively healthy sample (39).…”
Section: Some Individual Modifiable Risk Factors Differentially Influence Cognitive Decline and Riskmentioning
confidence: 99%